Rancangan Desain Tampilan Website Dinas Perpustakaan Dan Arsip Kota Balikpapan Menggunakan Kansei Engineering - Rizalmi, Sigit Rahmat; Maharani, Yuniar; Anggraini, Novita Lizza (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
The City Library and Archives Office utilizes its website to deliver information and services. However, its development has not yet considered user comfort and an adequate User Interface (UI) design, which reduces user satisfaction. This study aims to identify the elements that influence interface design and determine the reference specimen for UI design recommendations. The research employs the Kansei Engineering (KE) approach to connect user emotions with design elements. Data were collected through a questionnaire using 28 Kansei words to analyze five website specimens, involving 50 respondents. The analysis was conducted using Principal Component Analysis (PCA), Factor Analysis, and Partial Least Squares (PLS). The results indicate that the Kansei word "beautiful" has a dominant influence on user emotions (value: 0.995). The City Library and Archives Office of Riau’s website was identified as the most suitable reference specimen for the expected design concept. Design recommendations were formulated based on the PLS analysis, covering elements such as layout and color to ensure an optimal design. This study highlights the importance of emotional aspects in UI design to enhance user satisfaction and improve the effectiveness of information delivery.Keywords - Kansei Engineering, Multivariate Analysis, Partial Least Square, User Interface, Website.